The effect of cooperative learning model on elementary school students' learning motivation - Salamah, Evi Rizqi; Rifayanti, Zuni Eka Tiyas; Trisnawaty, Wulan (Prodi PGSD FKIP Universitas Islam Sultan Agung, 2024)
Solid motivation has a positive impact on learning achievement and student attainment. This study aimed to determine the impact of cooperative learning on learning motivation of grade IV students in Mojokerto, involving 72 elementary school students. The research method used was quantitative using Comparison-Group Design. The results showed significantly higher student learning motivation in the experimental group than in the control group. Cooperative learning was applied for the experimental group, while lecture-based teaching was used in the control group. Implications for innovation in teaching methods and further research are suggested to further popularize cooperative learning for better learning outcomes.